2012
DOI: 10.1111/j.1551-2916.2012.05398.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition and Electrical Properties of Ba0.7Ca0.3TiO3BiFeO3 Ceramics

Abstract: Lead-free piezoelectric ceramics of (1 À x)Ba 0.70 Ca 0.30 TiO 3 -x BiFeO 3 [(1 À x)BCT-xBF, x = 0-0.065] have been prepared and investigated. The ceramics with x 0.06 have diphasic tetragonal and orthorhombic crystal structures, whereas tetragonal phase is suppressed by the introduction of BF. As a result, the composition with x = 0.065 is found to have diphasic pseudocubic and orthorhombic phases. Significantly compositiondependent grain size is observed. With increasing x from 0 to 0.065, the ferroelectric-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Figure (b) shows the Δ T relax of the (1− x )BCT– x BF ceramics as a function of BF content. It is found that with x increases, the Δ T relax increases and reaches the maximum of 99 for x = 0.67, and then decreases, indicating that the degree of relaxor behavior is dependent on BF content in the (1− x )BCT– x BF ceramics, consistent with our previous report …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Figure (b) shows the Δ T relax of the (1− x )BCT– x BF ceramics as a function of BF content. It is found that with x increases, the Δ T relax increases and reaches the maximum of 99 for x = 0.67, and then decreases, indicating that the degree of relaxor behavior is dependent on BF content in the (1− x )BCT– x BF ceramics, consistent with our previous report …”
Section: Resultssupporting
confidence: 91%
“…(a). For x ≤ 0.07, the decrease in T m may be ascribed to decreased internal stress in increased grain size of T phase and the local random electric fields caused by the cosubstitution of A‐site Bi 3+ and B‐site Fe 3+ , which are consistent with our previous report . For x = 0.08–0.90, the change in T m may be interpreted based on the stress model .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Different cement matrix-based piezo composites like 0-3 and 2-2 with lead zirconium titanate (PZT) piezoelectric material have already been reported in the literature. [2,4,5] Experimental results demonstrated compatibility between cement and piezoelectric inclusions and the retention of piezoelectric properties for sensor applications ensuring the potential use of such composites for sensor applications. [6] Several researchers have verified and improved the compatibility of piezoelectric inclusions within cement matrices.…”
Section: Introductionmentioning
confidence: 99%
“…But such modes of operation may not be suitable in the case of concrete‐based material due to inherent differences in material properties and volume stability. [ 2 , 3 ] This motivated the development of cement‐based piezo composites to serve structural health monitoring purposes. Different cement matrix‐based piezo composites like 0–3 and 2–2 with lead zirconium titanate (PZT) piezoelectric material have already been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%